A randomised controlled trial of postal versus interviewer administration of a questionnaire measuring satisfaction with, and use of, services received in the year before death. Issue 12 (December 1998) - Addington-Hall, J; Walker, L; Jones, C; Karlsen, S; McCarthy, M
Abstract : STUDY OBJECTIVES: To develop a short form of an interview schedule used successfully in previous national surveys of care for the dying, and to investigate the effect of administering it by post on response rate, response bias and on the nature of responses to questions. DESIGN: Randomised controlled trial. SETTING: An inner London health authority. PARTICIPANTS: Informants (person registering death) of random sample of cancer deaths between June 1995 and July 1996. MAIN RESULTS: The shortened questionnaire (VOICES) has 158 questions. Response rate did not differ significantly between postal and interview groups (interview; 56% (69 of 123), postal: 52% (161 of 308). Responders in the two groups did not differ in terms of their sociodemographic characteristics. Postal questionnaires had significantly more missing data, particularly on questions about service provision and satisfaction with services. Responses to questions differed between the groups on 11 of 158 questions. Interview group respondents were more likely to give top ranking responses to questions on service satisfaction and symptom control. CONCLUSIONS: Postal questionnaires are an acceptable alternative to interviews in retrospective post-bereavement surveys of care for the dying, at least in terms of response rate and response bias. However, the increased costs of interview surveys need to be balanced against the fact that postal questionnaires result in more missing data, and possibly less reliable answers to some questions. Caution is needed in combining results from the two data collection methods as interview respondents gave more positive answers to some questions.